2015
DOI: 10.1371/journal.pone.0117487
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exopolysaccharide in Aggregatibacter actinomycetemcomitans–Induced Bone Resorption in a Rat Model for Periodontal Disease

Abstract: Aggregatibacter actinomycetemcomitans a causative agent of periodontal disease in humans, forms biofilm on biotic and abiotic surfaces. A. actinomycetemcomitans biofilm is heterogeneous in nature and is composed of proteins, extracellular DNA and exopolysaccharide. To explore the role played by the exopolysaccharide in the colonization and disease progression, we employed genetic reduction approach using our rat model of A. actinomycetemcomitans-induced periodontitis. To this end, a genetically modified strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 33 publications
2
35
0
1
Order By: Relevance
“…Notably, it was clearly shown that periodontal disease induces catabolic effects on alveolar bone homeostasis that are secondary to not only an increase in bone resorption, but also a decrease in bone formation (Baron & Saffar, ). Aggregatibacter actinomycetemcomitans LPS, leukotoxin, and to a lesser extent CdtB, PGA, and outer membrane protein 29 (OMP29) are virulence factors that have been shown to promote bone loss in preclinical rat models (Rogers et al ., ; Li et al ., ; Lin et al ., ; Yu et al ., ; Schreiner et al ., ; Shanmugam et al ., ).…”
Section: Aggregatibacter Actinomycetemcomitans Osteoimmuno‐modulatorymentioning
confidence: 97%
“…Notably, it was clearly shown that periodontal disease induces catabolic effects on alveolar bone homeostasis that are secondary to not only an increase in bone resorption, but also a decrease in bone formation (Baron & Saffar, ). Aggregatibacter actinomycetemcomitans LPS, leukotoxin, and to a lesser extent CdtB, PGA, and outer membrane protein 29 (OMP29) are virulence factors that have been shown to promote bone loss in preclinical rat models (Rogers et al ., ; Li et al ., ; Lin et al ., ; Yu et al ., ; Schreiner et al ., ; Shanmugam et al ., ).…”
Section: Aggregatibacter Actinomycetemcomitans Osteoimmuno‐modulatorymentioning
confidence: 97%
“…A murine periodontitis model combined with genomics and quantitative PCR was used to examine the role of host factors in persistent subgingival biofilms (336). Likewise, a rat model of A. actinomycetemcomitans-induced periodontitis was combined with RT-PCR for versatile applications, ranging from genetic reduction to therapeutic efficacy evaluation according to exopolysaccharide variations (367). Another rat model, the in vivo extraradicular biofilm model, is more inclusive, as it may facilitate identification and quantification of biofilm-forming bacteria by use of real-time PCR (rt-PCR) and micro-computed tomography (368).…”
Section: Vertebrate Animal Modelsmentioning
confidence: 99%
“…It has been shown, however, that Histophilus somni , a relative of H. influenzae , synthesizes an exopolysaccharide composed of a D-mannan polymer and with occasional Gal residues present on side chains during biofilm formation50, although the glycosyltrasferase(s) responsible for its synthesis has not been identified. Aggregatibacter actinomycetemcomitans , another member of Pasteurellaceae, also forms biofilms containing an extracellular homopolymer of N -acetylglucosamine residues in β(1 → 6) linkage that acts as an important virulence factor51.…”
Section: Discussionmentioning
confidence: 99%